How manipulating test scores affects school accountability and student achievement - Erich Battistin (IZA World of Labor, 2016)
Standardized testing has become the accepted means of measuring a school's quality. However, the associated rise in test-based accountability creates incentives for schools, teachers, and students to manipulate test scores. Illicit behavior may also occur in institutional settings where performance standards are weak. These issues are important because inaccurate measurement of student achievement leads to poor or ineffective policy conclusions. The consequences of mismeasured student achievement for policy conclusions have been documented in many institutional contexts in Europe and North America, and guidelines can be devised for the future.
Keywords: N3; 330; cheating; score manipulation; standardized testing